John Millar of Glasgow. 1735-1801. His life and thought and his contributions to sociological analysis. [With a forew. by R.M. MacIver] (Cambridge University Press, 1960)
With bibliogr., index and prt. Publications of the Department of Social and Economic Research, University of Glasgow. Ed.: A.K. Cairncross.